2007
DOI: 10.1007/s00192-006-0274-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anal sphincter laceration in 40,923 primiparous women

Abstract: The objective of this study was to identify factors associated with anal sphincter laceration in primiparous women. A subpopulation of 40,923 primiparous women at term with complete data sets was abstracted from a state-wide perinatal database in Germany. Outcome variable was anal sphincter laceration. Independent variables were 17 known obstetrical risk factors/conditions/interventions impacting childbirth recorded on the perinatal data collection sheet. Cross table analysis followed by logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…Whilst some authors have found a reduction in the rate of OASI with epidural analgesia [53][54][55], others have found no difference [12,41]. Roos et al [56] found that epidural analgesia was the only independent factor that predicted OASI.…”
Section: Epidural Analgesiamentioning
confidence: 99%
“…Whilst some authors have found a reduction in the rate of OASI with epidural analgesia [53][54][55], others have found no difference [12,41]. Roos et al [56] found that epidural analgesia was the only independent factor that predicted OASI.…”
Section: Epidural Analgesiamentioning
confidence: 99%
“…Curiously, these authors found that patients with a BMI less than 30 kg/m 2 had a greater chance of avulsion, and they hypothesized that nutritional status was related to this protective biomechanical effect of the pelvic muscles. However, their finding is still considered inconclusive 17,21 . Despite the small number of cases included in this study, 66% of the patients with levator ani muscle avulsion had a BMI less than 30 kg/m 2 , which coincide with the already presented data.…”
Section: Discussionmentioning
confidence: 96%
“…While the literature supports overweight as a risk factor for pelvic organ prolapse [23], other studies show a protective effect of higher BMI level on pelvic floor injury [24, 25]. …”
Section: Discussionmentioning
confidence: 99%